HAMBATAN PENYIDIK DALAM PENGGUNAAN TEKNIK UNDERCOVER BUY SEBAGAI UPAYA PENGUNGKAPAN TINDAK PIDANA NARKOTIKA DI POLDA BENGKULU - Albert Manalu; Sudirman Sitepu; Helda Rahmasari (Ensiklopedia of Journal, 2026)
The objective of this study is to analyse the obstacles to the use of the undercover buy technique as a means of investigating drug-related crimes at the Bengkulu Regional Police Headquarters. The research method is descriptive, falling under the category of empirical legal research. Research data was obtained from interviews with investigators at the Bengkulu Regional Police as primary data, whilst secondary data was obtained from a literature review. Research findings: The undercover buy technique is carried out by investigators from the Narcotics Directorate of the Bengkulu Regional Police based on implementation guidelines in the Chief of Police’s Decree (SKEP), namely SKEP/1205/IX/2000 (revised Technical Guidelines), whereby covert purchases were previously regulated under No.Pol. Juklap/04/VIII/1983 as an arrest procedure, as well as Law No. 35 of 2009 on Narcotics Offences.Keywords: Challenges Faced by Investigators, Narcotics, Undercover buy